The Impact of Changes in Long-Term Liabilities on the Stock Price of PT Aneka Tambang Tbk - Pranoto, Madeline Guenevere; Melodious, Heavenly; Elizabeth Tiur Manurung (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to examine the effect of long-term liabilities on the stock price of PT Aneka Tambang Tbk using the company’s financial data. In the mining industry, which is highly affected by commodity price fluctuations and large capital requirements, long-term liabilities serve as an important financing source to support business expansion and operational activities. However, increasing long-term liabilities may also raise the company’s financial risk, which can influence investor perception and stock price movements. This research uses long-term liabilities and stock price data of PT Aneka Tambang Tbk from 2017 to 2024 with a total of 30 observations. A simple linear regression method is applied to analyze the relationship between long-term liabilities as the independent variable and stock price as the dependent variable. The results show that long-term liabilities have a negative and statistically significant effect on the stock price, with a regression coefficient of -2.53516×10⁻⁷ and a p-value of 7.0484×10⁻⁶, which is below the 0.05 significance level. This indicates that an increase in long-term liabilities tends to be negatively perceived by the market. The Adjusted R Square value of 0.5023 suggests that approximately 50.23% of the variation in PT Aneka Tambang Tbk’s stock price can be explained by changes in long-term liabilities, while the remaining variation is influenced by other factors such as global commodity prices, operational performance, government policies, and investor sentiment. Therefore, this study highlights the importance of prudent management of long-term liabilities, as it plays a significant role in maintaining the market value and investor confidence in PT Aneka Tambang Tbk